Analisis Peran Celebrity Endorser, Brand Image, dan Lifestyle dalam Memengaruhi Keputusan Pembelian Konsumen : Studi Kasus pada Pengguna Honda Scoopy - Nida, Nadhivatun; Titin Hargyatni (BADAN PENERBIT STIEPARI PRESS, 2025)
Consumer purchasing decisions are influenced by various factors, including brand image, celebrity endorsements, and lifestyle. In the motorcycle industry, particularly for the Honda Scoopy brand, understanding how these factors influence consumer decisions is crucial. This study aims to identify and analyze the impact of celebrity endorsers, brand image, and lifestyle on purchasing decisions of Honda Scoopy motorcycles in Bumiayu, Brebes. To achieve this, a quantitative associative approach was employed, with data collected through questionnaires distributed to 96 respondents. The data collected were analyzed using multiple linear regression with the assistance of Microsoft Excel software. The results indicate that lifestyle significantly influences purchasing decisions for Honda Scoopy motorcycles. In contrast, celebrity endorsers and brand image did not show a significant effect on purchasing decisions on a partial basis. However, simultaneously, all three variables had a significant impact on purchasing decisions. The implications of these findings suggest that a deep understanding of consumer lifestyle is a key factor in designing effective marketing strategies. Therefore, it is recommended that companies focus their strategies on aligning products with consumer lifestyles and strengthen the lifestyle element in marketing communications, despite the insignificant influence of celebrity endorsers and brand image in this study.